2021
DOI: 10.1002/jctb.6697
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the microbial community in a biotrickling filter treating a complex mixture of gaseous compounds causing odor nuisance

Abstract: BACKGROUND Industrial gaseous emissions causing odor nuisance has become a major environmental issue in many countries. Biotrickling filters are suitable for treating mixtures of gaseous compounds with high removal efficiencies. The aim of this work was to determine the vertical distribution of microbial communities established in a biotrickling filter treating a mixture of gaseous compounds causing odor nuisance, and to correlate its performance with the spatial and temporal distribution of inoculated bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In turn, this implies that a large flow of water would be required. On the other hand, biofiltration of contaminated gaseous streams has been successfully applied to the abatement of arenes such as toluene, benzene, styrene and xylene, 8‐12 and the treatment of nitrogen‐containing pollutants such as triethylamine 13,14 . On the contrary, there are no reports on the biofiltration of pyrazines or alkylpyrazines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, this implies that a large flow of water would be required. On the other hand, biofiltration of contaminated gaseous streams has been successfully applied to the abatement of arenes such as toluene, benzene, styrene and xylene, 8‐12 and the treatment of nitrogen‐containing pollutants such as triethylamine 13,14 . On the contrary, there are no reports on the biofiltration of pyrazines or alkylpyrazines.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, biofiltration of contaminated gaseous streams has been successfully applied to the abatement of arenes such as toluene, benzene, styrene and xylene, [8][9][10][11][12] and the treatment of nitrogen-containing pollutants such as triethylamine. 13,14 On the contrary, there are no reports on the biofiltration of pyrazines or alkylpyrazines. As recognized by Rappert and Müller, 15 a prime requirement for the design of biofiltration units for the treatment of these odorous compounds is an understanding of the capabilities of microbes for their degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Sun reported that ceramic pellets were used as packing material to establish a BTF to purify waste gas containing styrene, and results indicated that the removal efficiency (RE) of styrene could be reached up to 95% [11]. Aguirre reported that in BTF, the removal efficiencies were 100% for ammonia and H 2 S, 73% for methanol, 63% for trimethylamine, 41% for dimethylsulphide, and 32% for 2,5-dimethylpirazyne at day 538, respectively [12]. Previous studies have proven that volatile organic pollutants can be degraded by BTF.…”
Section: Introductionmentioning
confidence: 99%